Efektivitas Pelaksanaan Fungsi Dinas Pekerjaan Umum dan Penataan Ruang Kabupaten Sumba Timur dalam Mengelola Irigasi di Kecamatan Kambera Kabupaten Sumba Timur Berdasarkan Peraturan Pemerintah Nomor 20 Tahun 2006 tentang Irigasi - Dwi Sari Rambu Andu Uma Ndjurumbaha; Josef Mario Monteiro; Rafael Rape Tupen (LPPM Universitas Sains dan Teknologi Komputer, 2024)
The purpose of this study was to determine and analyze the effectiveness of the implementation of the functions of the public works and spatial planning offices in managing irrigation in Kambera District, East Sumba Regency. To determine the factors inhibiting the effectiveness of the implementation of the functions of the public works and spatial planning offices in managing irrigation in Kambera District, East Sumba Regency. The type of research used by this researcher is empris juridical method and the data is analyzed descriptively qualitative in which the focus of the research is procurement planning, implementation, supervision, and accountability of irrigation management, as well as inhibiting factors, namely research whose data is directly obtained from the research location of 13 resource persons. The results of this study indicate that the implementation of the functions of the Public Works and Spatial Planning department in irrigation management in Kambera District, East Sumba Regency, starting from planning, implementation, supervision, accountability of irrigation management that has not been done optimally. Factors inhibiting the implementation of the functions of the Public Works and Spatial Planning Office in managing irrigation in Kambera District, East Sumba Regency include: human resources of ASNs within the Public Works and Spatial Planning Office, especially the Water Resources sector which is lacking in both quality and quantity, inadequate facilities and infrastructure factors and a budget that is lacking and not in accordance with the needs.